An Existence Principle for Nonlocal Difference Boundary Value Problems with φ-Laplacian and Its Application to Singular Problems. (3rd February 2008) - Agarwal, Ravi P.; O'Regan, Donal; Stanêk, Svatoslav
Abstract : The paper presents an existence principle for solving a large class of nonlocal regular discrete boundary value problems with theφ -Laplacian. Applications of the existence principle to singular discrete problems are given.